Analisis Penerapan Konseling Singkat Berbasis Solusi terhadap Regulasi Emosi Anak SD Margajaya Ciawi Tasikmalaya - Nijma Nailah; Ari Firmansyah; Reyfa Nurdin; Santi Sintiani; Sri Mulyani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Emotion regulation is an essential skill that should be developed among elementary school students because it influences the learning process, social interactions, and psychological development. This skill enables students to recognize, understand, and express their emotions appropriately in various situations. However, not all students are able to regulate their emotions effectively, highlighting the need for guidance and counseling services that are appropriate to their developmental stage. One approach that can be implemented is Solution-Focused Brief Counseling (SFBC), which emphasizes individuals' strengths and potential in addressing the challenges they face. This study aimed to investigate the implementation of Solution-Focused Brief Counseling in supporting the emotion regulation of students at SD Margayaja, Cipacing, Ciawi, Tasikmalaya. The study employed a qualitative method involving classroom teachers as informants to describe students' responses following the counseling sessions. Data were collected through classroom observations and teachers' assessments of students' behavioral changes. The findings indicated improvements in students' ability to manage anger, express emotions constructively, build positive social relationships, adapt to school interactions, and collaborate with their peers. Therefore, Solution-Focused Brief Counseling has the potential to serve as a routine intervention and a practical alternative counseling service in elementary schools. Future research is recommended to employ more in-depth qualitative approaches to further examine the effectiveness of this method.